Influence of Brand Product Quality, Price and Promotion on the Decision to Purchase You C1000 Products - Anggraeni, Dewi; Karach, Ramadiansyah Anasan (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study's objective was to investigate the ways in which variables including PROQUALITY , marketing, and pricing affected the decisions of potential buyers to purchase YOU C1000 goods. In this study, the causality technique is employed to clarify the relationship between the variables. A survey that was done a for the research employed a survey as a research technique. During the data analysis phase of this investigation, quantitative statistical techniques were used to test the predefined hypotheses. Data analysis and processing with SPSS software. 150 respondents who utilize YOU C1000 in Jabodetabek make up the study's sample. The Calculator Sample Size Convident Interval is the sampling method that is employed. Tests for multicollinearity, heteroscodesticity, and normalcy are used in this research. To examine data, multiple linear regression analysis is used. The study's findings indicate that, When taken collectively, PROQUALITY , pricing, and marketing have a favorable and significant impact on purchasing decisions, A person's decision to buy is positively and significantly impacted by the quality of the product, Product costs have a favorable and large impact on decisions to buy on an individual basis, Promotions have a positive and considerable impact on individual purchase decisions.